Angiographic characteristics in Moyamoya disease with the p.R4810K variant: a propensity score‐matched analysis. (16th March 2020) - Ge, P.; Zhang, Q.; Ye, X.; Liu, X.; Deng, X.; Wang, J.; Wang, R.; Zhang, Y.; Zhang, D.; Zhao, J.
Abstract : Background and purpose: The p.R4810K variant was identified as a strong susceptibility in patients with Moyamoya disease (MMD). The aim of this study was to investigate the angiographic characteristics in MMD with the p.R4810K variant. Methods: Angiographic characteristics were compared between patients with wild‐type p.R4810K variant (GG) and patients with heterozygous p.R4810K variant (GA) after 1:1 propensity score matching, including Suzuki stage, collateral circulation and external carotid artery (ECA) collateral. Collateral circulation was graded with scores ranging from 0 to 12: posterior collateral circulation from the posterior cerebral artery to the middle cerebral artery and anterior cerebral artery was scored from 0 to 6; anterior collateral circulation was scored as 6 to 0 corresponding to Suzuki stages 0 to 6. Results: A total of 489 patients were screened; 133 pairs were obtained after 1:1 propensity score matching. Compared with the patients in the GA group, unilateral MMD was more frequent in the GG group ( P  = 0.026). Hemispheres in the GA group (86/266) had more posterior cerebral artery involvement than hemispheres in the GG group (48/266) ( P  < 0.001). Hemispheres in the GA group had a lower grade in collateral circulation than hemispheres in the GG group ( P  = 0.011), but ECA collateral was more frequently observed in the GA group than in the GG group (53.4% vs. 39.8%, P  = 0.002). Superficial temporal artery and occipital artery collateral was more frequently observed in the GA group than in the GG group ( P  < 0.05). Conclusions: Patients in the GA group had lower grades in collateral circulation than patients in the GG group, but ECA collateral was more frequently observed in the GA group than in the GG group.